Inside Cover: Probing Charge Transfer in Benzodifuran–C60 Dumbbell‐Type Electron Donor–Acceptor Conjugates: Ground‐ and Excited‐State Assays (ChemPhysChem 13/2013). Issue 13 (12th September 2013) - Li, Hui; Schubert, Christina; Dral, Pavlo O.; Costa, Rubén D.; La Rosa, Andrea; Thüring, Jürg; Liu, Shi‐Xia; Yi, Chenyi; Filippone, Salvatore; Martín, Nazario; Decurtins, Silvio; Clark, Timothy; et al.
<x xml:space="preserve">Abstract</x> A series of electron‐accepting fullerene dumbbells featuring different molecular linkers to electron‐donating benzodifuran is described on p. 2910 by D. M. Guldi, S.‐X. Liu et al.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>